Implementation of fuzzy logic controller-based quadratic buck converter for LED lamp driver applications. (30th April 2020) - Yadlapalli, Ravindranath Tagore; Kotapati, Anuradha
This paper presents the design of quadratic buck converter (QBC) for LED lamp driver applications. The LED current regulation is the critical issue in the family of LED lamp drivers. The continuous conduction mode-based quadratic buck converter is well designed for 60 V/20 mA at 100 kHz. The quadratic buck converter performance is analysed with digital-average current mode control-based quadratic buck converter and also fuzzy-average current mode control-based quadratic buck converter. The simulation is accomplished using MATLAB/Simulink software.